THE NATURE AND SIGNIFICANCE OF THE RIGHT TO BODILY INTEGRITY. (8th August 2017) - Herring, Jonathan; Wall, Jesse
Abstract: This article seeks to explain and explore the concept of bodily integrity. The concept is often elided with autonomy in the case law and the academic literature. It argues that bodily integrity is non-reducible to the principle of autonomy. Bodily integrity relates to the integration of the self and the rest of the objective world. A breach of it, therefore, is significantly different to inteference in decisions about your body. This explains why interference with bodily integrity requires justification beyond what will suffice for an interference with autonomy. It also explores how this understanding of bodily integrity assists in understanding disability, gender and separated bodily material.